Pokemon proto‐oncogene in oral cancer: potential role in the early phase of tumorigenesis. (19th January 2015) - Sartini, D; Lo Muzio, L; Morganti, S; Pozzi, V; Di Ruscio, G; Rocchetti, R; Rubini, C; Santarelli, A; Emanuelli, M
<x xml:space="preserve">Abstract</x> Objectives Oral squamous cell carcinoma (OSCC) represents about 90% of all oral neoplasms with a poor clinical prognosis. To improve survival of OSCC patients, it is fundamental to understand the basic molecular mechanisms characterizing oral carcinogenesis. Dysregulation of oncogenes and tumor suppressor genes seems to play a central role in tumorigenesis, including malignant transformation of the oral cavity. Materials and Methods We analyzed the expression levels of the pro‐oncogenic transcription factor Pokemon through real‐time PCR, Western blot and immunohistochemistry in tumor, and normal oral tissue samples obtained from 22 patients with OSCC. The relationship between tumor characteristics and the level of Pokemon intratumor expression was also analyzed. Results Pokemon was significantly downregulated in OSCC. In particular, both mRNA and protein levels (tumor vs normal tissue) inversely correlated with histological grading, suggesting its potential role as a prognostic factor for OSCC. Moreover, a significant inverse correlation was found between Pokemon protein expression levels (OSCC vs normal oral mucosa) and tumor size, supporting the hypothesis that Pokemon could play an important role in the early phase of tumor expansion. Conclusion This work shows that reduced expression of Pokemon is a peculiar feature of OSCC. Additional studies may establish the effective role of Pokemon in oral tumorigenesis.